Effects of Intermittent Neck Cooling During Repeated Bouts of High-Intensity Exercise - Andrew J. Galpin; James R. Bagley; Blake Whitcomb; Leonard D. Wiersma; Jakob Rosengarten; Jared W. Coburn; Daniel A. Judelson (MDPI AG, 2016)
The purpose of this investigation was to determine the influence of intermittent neck cooling during exercise bouts designed to mimic combat sport competitions. Participants (n = 13, age = 25.3 ± 5.0 year height = 176.9 ± 7.5 cm, mass = 79.3 ± 9.0 kg, body fat = 11.8% ± 3.1%) performed three trials on a cycle ergometer. Each trial consisted of two, 5-min high-intensity exercise (HEX) intervals (HEX1 and HEX2-20 s at 50% peak power, followed by 15 s of rest), and a time to exhaustion (TTE) test. One-minute rest intervals were given between each round (RI1 and RI2), during which researchers treated the participant's posterior neck with either (1) wet-ice (ICE); (2) menthol spray (SPRAY); or (3) no treatment (CON). Neck (TNECK) and chest (TCHEST) skin temperatures were significantly lower following RI1 with ICE (vs. SPRAY). Thermal sensation decreased with ICE compared to CON following RI1, RI2, TTE, and a 2-min recovery. Rating of perceived exertion was also lower with ICE following HEX2 (vs. CON) and after RI2 (vs. SPRAY). Treatment did not influence TTE (68.9 ± 18.9s). The ability of intermittent ICE to attenuate neck and chest skin temperature rises during the initial HEX stages likely explains why participants felt cooler and less exerted during equivalent HEX bouts. These data suggest intermittent ICE improves perceptual stress during short, repeated bouts of vigorous exercise.